Jokowi, Masalah Ketidakmerataan dan Demokrasi di Indonesia - Edward Aspinall (SIASAT, 2018)
The new president, Joko Widodo, won elections in 2014 by mobilizing support from the poor, presenting himself as someone who was uniquely able to understand the needs of the poor and offering them wider health care, education, and various services other social. One of the earliest policies was the distribution of aid programs to poor families which would eventually reach one third of Indonesia's population, making this program, according to The Economist magazine, "the largest of similar programs around the world.